Reimagining the 4M Framework in Educational Development for SoTL - Mandy Frake-Mistak; Jennifer Friberg; Melanie Hamilton (Teaching & Learning Inquiry: The ISSOTL Journal, 2023)
In this paper, we seek to contextualize our work in SoTL-focused educational development and those who work to support others in SoTL, as interstitially spaced across the 4M Framework, re-envisioned as a flexible but formalized professional continua. The establishment of a model for educational development SoTL-related activity allows for the opportunity to explore how this work is done in a systematic manner. We offer our ideas and visions through, what we term, the 4M Continua for Educational Development as a possible understanding of the work that SoTL-focused educational developers do, as well as those who engage in educational development more broadly. While the 4M Framework provides a guide through four interrelated organizational lenses: micro; meso; macro; and mega, we have adapted a model to situate educational development work using the 4M Framework to inform the ways in which we do, contribute to, consume, advocate, and support SoTL broadly, including at local, provincial, national, and international levels. The 4M Continua can be an avenue for those who do educational development to describe their work, where the work is situated, and how support can be offered throughout the community.